2015
DOI: 10.1155/2015/301949
|View full text |Cite
|
Sign up to set email alerts
|

Profunda Femoris Pseudoaneurysm following Total Hip Arthroplasty Revision

Abstract: Vascular injuries following total hip arthroplasty (THA) are very rare, with pseudoaneurysm being a small subset. We report a case of profunda femoris artery (PFA) pseudoaneurysm in a 61-year-old male following a posterior approach revision left THA. Presentation involved continued blood transfusion requirements several weeks postoperatively. Diagnosis of the pseduoaneurysm was made by contrast CT of the lower extremity, with confirmation via IR angiography. Successful embolization was achieved with selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…In this scenario, different types of vascular complications have been reported in medical literature, mainly in the form of case reports: vessel laceration, haemorrhage, vascular compression, intimal flap tear, pseudoaneurysm, arteriovenous aneurysm, arterial thromboembolism, and ligation [4][5][6][7][8][9][10][11][12][13][14]20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, different types of vascular complications have been reported in medical literature, mainly in the form of case reports: vessel laceration, haemorrhage, vascular compression, intimal flap tear, pseudoaneurysm, arteriovenous aneurysm, arterial thromboembolism, and ligation [4][5][6][7][8][9][10][11][12][13][14]20].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature this scenario has been reported mainly in the form of case reports concerning vascular complications of a specific orthopaedic intervention [4][5][6][7][8][9][10][11][12][13][14]; this paper aims to evaluate the safety and efficacy of endovascular embolisation in a series of patients presenting with arterial injuries of the lower limbs following orthopaedic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The femoral artery courses into the leg through the femoral triangle before splitting into the superficial femoral artery and the profunda femoris [ 5 ]. The superficial femoral artery goes on to supply 5 branches: the superficial circumflex iliac, superficial epigastric, superficial external pudendal, deep external pudendal, and descending genicular artery [ 5 , 6 ]. The profunda femoris then terminates within the thigh, never leaving the region [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another incident in the literature concerning PFA pseudoaneurysm following total hip arthroplasty, described by Huynh et al, suggested that inappropriate use of the Hohmann retractor was again the source of the injury [ 14 ]. Harper et al suggested a more complex etiology of PFA injury during hip arthroplasty possibly resulting from a stretch injury to the vasculature of the region [ 6 ]. This etiology of injury would be similar to lateral femoral cutaneous nerve palsies that have been known to occasionally result from stretch injuries during hip arthroplasty positioning [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation